2017
DOI: 10.1074/jbc.m116.763680
|View full text |Cite
|
Sign up to set email alerts
|

The DNA replication protein Cdc6 inhibits the microtubule-organizing activity of the centrosome

Abstract: The centrosome serves as a major microtubule-organizing center (MTOC). The Cdc6 protein is a component of the pre-replicative complex and a licensing factor for the initiation of chromosome replication and localizes to centrosomes during the S and G phases of the cfell cycle of human cells. This cell cycle-dependent localization of Cdc6 to the centrosome motivated us to investigate whether Cdc6 negatively regulates MTOC activity and to determine the integral proteins that comprise the pericentriolar material (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
(65 reference statements)
1
12
0
Order By: Relevance
“…CDC6 is situated at chromosome 17q21.3, controlling the S‐stage‐inducing factors. CDC6 was considered as the key to DNA replication . As reported in the literature, CDC6 could inhibit DNA replication and induce cell apoptosis .…”
Section: Discussionsupporting
confidence: 72%
“…CDC6 is situated at chromosome 17q21.3, controlling the S‐stage‐inducing factors. CDC6 was considered as the key to DNA replication . As reported in the literature, CDC6 could inhibit DNA replication and induce cell apoptosis .…”
Section: Discussionsupporting
confidence: 72%
“…γ-tubulin is a major component of MTOCs and it is important for nucleating microtubules (Sobel & Snyder, 1995). A recent study showed that CDC6 localizes to centrosomes during the S-and G2-phases of the cell cycle of human cells, and it inhibits the microtubule-organizing activity of the centrosome in mitosis (Lee et al, 2017). In the present study, we found that CDC6 Depletion of CDC6 resulted in displacement of γ-tubulin from spindle poles, implying that CDC6 may contribute to spindle organization by partially impairing the function of MTOCs.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse CDC6 binds chromatin and associates with the spindle during mitosis. A recent study suggests a novel function for CDC6 in coordinating centrosome assembly and function (Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that CDC6 inhibits the microtubule-organizing activity of the centrosome in mitosis (Lee et al, 2017). In Hela cells, phosphorylation of CDC6 by Plk1 is required for CDK1 and cyclin B inhibition, which is necessary for separase activation and exit from mitosis (Hyungshin and Erikson, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mouse CDC6 binds chromatin and associates with the spindle during mitosis. A recent study suggests a novel function for Cdc6 in coordinating centrosome assembly and function (Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%